2006
DOI: 10.5194/aab-49-259-2006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of association of GPX5, FUT1 and ESR2 genotypes with litter size in a commercial pig cross population

Abstract: The aim of this study was to investigate, if special genotypes of the genes glutathione peroxidase 5 (GPX5), fucosyltransferase 1 (FUT1) and estrogen receptor 2 (ESR2) are associated with litter size in a commercial pig cross population. For this purpose, a total of 123 F 2 sows were divided into two extreme performance groups, one with a high litter size (n = 61, ≥ 14.3 piglets per litter) and one with a low litter size (n = 62, ≤ 11.3 piglets per litter) and genotyped using PCR-RFLP methods. The Chi-square t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Conducted analysis showed that animals with 2B2B genotype characterized higher ejaculate volume, sperm alive percentage, live sperm content and number of insemination doses in respect to 1B1B genotype (Kmie et al, 2007). Other results showed that 2B2B genotype is associated with better quality of semen but it depends on breed as well as it is not associated with litter size (Mackowski et al, 2004;Buske et al, 2006). Latest investigations showed that GPX5 gene variants are associated with number of functional teats in Italian Large White pigs (Dall'Olio et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conducted analysis showed that animals with 2B2B genotype characterized higher ejaculate volume, sperm alive percentage, live sperm content and number of insemination doses in respect to 1B1B genotype (Kmie et al, 2007). Other results showed that 2B2B genotype is associated with better quality of semen but it depends on breed as well as it is not associated with litter size (Mackowski et al, 2004;Buske et al, 2006). Latest investigations showed that GPX5 gene variants are associated with number of functional teats in Italian Large White pigs (Dall'Olio et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In the examined wild boars, the 1B1B genotype frequency was somewhat higher in relation to above mentioned Duroc x Pietrain crossbred. In the case of investigations carried out by Buske et al (2006) on crossbred (Large White) sows x Leicome boars, the 1B1B genotype had also the lowest frequency (0.06). Heterozygous genotype however occurred with lower frequency, while 2B2B genotype with higher frequency in comparison to wild boars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For GPX5 and FUT 1 genes primers, as reported by Buske et al (2006) China). Mter denaturation at 94C for 2 min, 30 amplification cycles comprising denaturation at 94C for 1 min, annealing at appropriate temperature (55-60C) for 30 s, and extension at 72C for 40 s were performed followed by a final 5 min extension step at 72C.…”
Section: Methodsmentioning
confidence: 99%
“…The ESR gene has been considered as one of the most promising gene marker. When this marker started to be studied in different populations the results began to be no homogeneous, for example BUSKE et al (2006), DRÖGENMÜLLER et al (1999 DEPUDYPT et al (1999) or HUMPOLICEK et al (2006. The study was performed under commercial conditions and the results outlined the usefulness of creation of HP population.…”
Section: Resultsmentioning
confidence: 99%